More than I love my life : a novel - Grossman, David (Alfred A. Knopf, 2021)
"From the internationally best-selling author--and revered moral voice--a remarkable novel of suffering, love, and healing, the story of three generations of women and a secret that needs to be told. The story was inspired by the life of a friend and confidante of David Grossman who, in the late 1940s, was imprisoned and tortured on the notorious Goli Otok, a barren island prison off the coast of Croatia. Grossman's telling focuses on three strong women--Vera, 90; her daughter, Nina; and her granddaughter, Gili, who at 39 years old is a filmmaker and a wary consumer of affection. A bitter secret divides each mother and daughter pair, though Gili--abandoned when she was just three by Nina--has been close to her grandmother throughout her life. With Gili making the arrangements, they travel together back to Goli ("the Adriatic Alcatraz"), where Vera was imprisoned, enslaved, and tortured for three years as a young wife, when she refused to betray her husband and denounce him as an enemy of the people. This unlikely journey, documented by Gili's camera, lays bare the intertwining of fear, love, and mercy, and the complex overlapping demands of romantic and parental passion. With flashbacks to the stalwart Vera protecting what was most precious on the wretched rock where she was held, and Grossman's fearless examination of the human heart, this swift novel will thrill his many readers and bring new ones into the fold"--